2021
DOI: 10.1093/heapro/daaa140
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, a tale of two pandemics: novel coronavirus and fake news messaging

Abstract: Summary The emergence of COVID-19, caused by novel Coronavirus SARS-CoV-2, became a pandemic in just 10 weeks. Without effective medications or vaccines available, authorities turned toward mitigation measures such as use of face masks, school’s closings, shelter-in-place, telework and social distancing. People found refuge on the internet and social media apps; however, there was a proliferation of instant messaging containing hoaxed, deliberate misleading information: fake news messaging (FNM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 28 publications
0
40
0
8
Order By: Relevance
“…However, it should be noted that information seeking about COVID-19 and risk perception may reciprocally interact with each other [47]. Previous research showed that health-related misleading and false information is often shared through social media [33,48,49]. Political conservatism [32], relying on social media for COVID-19 information [32,33], and lack in trust in health authorities [50] are clearly linked to an increased susceptibility to misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that information seeking about COVID-19 and risk perception may reciprocally interact with each other [47]. Previous research showed that health-related misleading and false information is often shared through social media [33,48,49]. Political conservatism [32], relying on social media for COVID-19 information [32,33], and lack in trust in health authorities [50] are clearly linked to an increased susceptibility to misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that developing models predicting vaccine adherence or hesitancy based on easy-to-collect data not related to a specific disease or treatment delivers highquality outputs (around 85%). Our predictive machine-learning models can support health communication policies to improve the dissemination and the impact of evidence-based information on vaccines and vaccination [38,39].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Web can be used for spreading misinformation and hate speech on COVID-19 information. AI-based tools play a vital role in fighting against hate speech ( Atehortua & Patino, 2021 ).…”
Section: Social Implicationsmentioning
confidence: 99%